2019
DOI: 10.14449/jbd.2019.7.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Standardized Uptake Value of 18F-fluorodeoxyglucose Positron Emission Tomography-Computed Tomography in Assessing Axillary Lymph Node Metastasis in Different Subtypes of Breast Cancer

Abstract: This study aimed to examine the association between the maximum standardized uptake value (SUVmax) of different molecular subtypes of primary breast cancer with axillary lymph node (ALN) metastasis. Methods: The medical records of 633 patients, who underwent 18F-fluorodeoxyglucose positron emission tomography-computed tomography (PET/CT) for preoperative staging, were retrospectively reviewed. The cohort was stratified by the following molecular subtypes with immunohistochemical examination: luminal A, luminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…found that a high tumor SUVmax (≥4.25) predicted axillary lymph node metastasis in ER-positive/HER2 negative and HER2 positive subtypes, but not in the triple-negative subtype [14]. And another study showed that tumor SUVmax could predict lymph node metastasis only in luminal A and HER2 positive type but not in luminal B and triple-negative type [15]. In contrast, the other study reported that PET-CT was a useful imaging tool in predicting lymph node metastasis in the triple-negative subtype compared to the other three subtypes, with a sensitivity of 87% and specificity of 67% [16].…”
Section: Discussionmentioning
confidence: 99%
“…found that a high tumor SUVmax (≥4.25) predicted axillary lymph node metastasis in ER-positive/HER2 negative and HER2 positive subtypes, but not in the triple-negative subtype [14]. And another study showed that tumor SUVmax could predict lymph node metastasis only in luminal A and HER2 positive type but not in luminal B and triple-negative type [15]. In contrast, the other study reported that PET-CT was a useful imaging tool in predicting lymph node metastasis in the triple-negative subtype compared to the other three subtypes, with a sensitivity of 87% and specificity of 67% [16].…”
Section: Discussionmentioning
confidence: 99%